Pengaruh Implementasi E-Budgeting dan E-Procurement Terhadap Efisiensi Belanja Daerah dalam Akuntansi Keuangan Sektor Public - Nurhuda Ardillah; Antong Antong; Junaidi Junaidi (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study aims to determine the effect of e-budgeting and e-procurement implementation on regional spending efficiency in the context of public sector financial accounting. The study used a quantitative approach, with a population of all Regional Apparatus Organizations (OPD) in Palopo City, while the sample was determined using a purposive sampling technique of 60 respondents. Data were collected through questionnaires and analyzed using multiple linear regression using SPSS. The results indicate that e-budgeting and e-procurement have a significant effect on regional spending efficiency. The implementation of both systems has been shown to increase transparency, data accuracy, and the effectiveness of the budgeting and procurement processes. The implications of this study indicate that digital transformation in the public financial system is a strategic step in realizing efficient, transparent, and accountable budget governance. Therefore, local governments need to improve the competence of their apparatus and strengthen their technological infrastructure to optimize the implementation of both systems to support regional spending efficiency.